ADMINISTRASI PEMBELAJARAN DI KELAS INKLUSI DAN KELAS KLASIFIKASI - Nuraini Nuraini (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Administration is the activity of systematically compiling and recording data and information that aims to provide various information and also make it easier to retrieve it in part or in whole. Teaching administration in inclusive classes and special classification classes in primary schools, there are several administrations that must be completed by teachers whose administration consists of: educational calendar, annual program, semester program, syllabus, SK / KD analysis, assessment procedures, lesson plans, KKM, journals teacher agendas, attendance books, grade lists, handbooks (textbooks, modules, worksheets), teaching materials, question grids, question cards, analysis of test results, remedial programs, enrichment programs, question sets. In general, the administration in the inclusive class and the classification class is the same, but what distinguishes the heterogeneous conditions of the students in the inclusion class is that the teacher separates the administration between regular students and inclusive students. While the administration in the class classification of the condition of the students is homogeneous there is no administrative separation.